2018
DOI: 10.1182/blood-2018-99-111628
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Sec23b in COPII Vesicles Regulates T Cell Immunity

Abstract: T cells play critical roles in both protective and pathogenic adaptive immune responses. The release of cytokines by T cells is critical for their development, differentiation, and effector functions. However, significant gaps remain in our understanding of the fundamental cellular and molecular pathways that are critical for T cell cytokine release. Coat Protein Complex II (COPII) enables protein transport from the endoplasmic reticulum (ER) to the Golgi apparatus. It consists of an outer layer that facilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Recently, we have begun to decipher the role of the COPII pathway in the release of cytokines by T cells. We observed that disrupting COPII coat formation by targeting SEC23 results in greatly reduced pathogenicity of donor T cells in experimental models of GVHD (120). Future studies on how the COPII pathway regulates secretion of critical Signal 3 cytokines may further shed light on immune cell secretory pathways and provide insight into potential novel therapeutic targets.…”
Section: Targeting Early Intracellular Phases Of the Efferent Arm Of Signal 3 Releasementioning
confidence: 84%
“…Recently, we have begun to decipher the role of the COPII pathway in the release of cytokines by T cells. We observed that disrupting COPII coat formation by targeting SEC23 results in greatly reduced pathogenicity of donor T cells in experimental models of GVHD (120). Future studies on how the COPII pathway regulates secretion of critical Signal 3 cytokines may further shed light on immune cell secretory pathways and provide insight into potential novel therapeutic targets.…”
Section: Targeting Early Intracellular Phases Of the Efferent Arm Of Signal 3 Releasementioning
confidence: 84%